2017
DOI: 10.1016/j.neuroscience.2017.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Improved proprioceptive function by application of subsensory electrical noise: Effects of aging and task-demand

Abstract: The application of subsensory noise stimulation over the lower limbs has been shown to improve proprioception and postural control under certain conditions. Whereas the effect specificity seems to depend on several factors, studies are still needed to determine the appropriate method for training and rehabilitation purposes. In the current study, we investigated whether the application of subsensory electrical noise over the legs improves proprioceptive function in young and older adults. We aimed to provide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
0
22
1
1
Order By: Relevance
“…Assessing one's multisensory capabilities (e.g., width of the temporal window of integration) would, therefore, allow for the early detection and intervention by introducing multisensory perceptual training paradigms that can narrow the temporal window of integration, refine older adults’ temporal discrimination abilities of auditory and visual stimuli, and, consequently, reduce susceptibility to audiovisual illusions (i.e., improving accuracy), as it has been already shown in young individuals . The latter finding suggests that multisensory temporal discrimination training can generalize to other perceptual processes that are not directly trained, and probably yield transfer effects to the motor domain, thus reducing the fall‐risk in older adults, ameliorating the common age‐related gait and postural deficits, and ensuring low gait variability …”
Section: Exploiting the Benefits Of Multisensory Processing For Succementioning
confidence: 88%
“…Assessing one's multisensory capabilities (e.g., width of the temporal window of integration) would, therefore, allow for the early detection and intervention by introducing multisensory perceptual training paradigms that can narrow the temporal window of integration, refine older adults’ temporal discrimination abilities of auditory and visual stimuli, and, consequently, reduce susceptibility to audiovisual illusions (i.e., improving accuracy), as it has been already shown in young individuals . The latter finding suggests that multisensory temporal discrimination training can generalize to other perceptual processes that are not directly trained, and probably yield transfer effects to the motor domain, thus reducing the fall‐risk in older adults, ameliorating the common age‐related gait and postural deficits, and ensuring low gait variability …”
Section: Exploiting the Benefits Of Multisensory Processing For Succementioning
confidence: 88%
“…The authors suggested that mechanical noise may constitute a means of improving postural stability in subjects with sensory deficits. Similarly, electrical noise stimulation applied over the knee or leg muscles improved proprioception and postural control in young and older adults (Gravelle et al 2002;Toledo et al 2017).…”
Section: Perspectivesmentioning
confidence: 99%
“…e strength of the signal, which is interpreted as noise, is below conscious perception; therefore, subjects are not aware of its presence. is kind of stimuli decreases vibratory threshold detection in young [13] and elderly persons [14], enhances kinesthetic perception [15] and joint position sense [10], and decreases postural sway when skin receptors in the area above the muscles that stabilize posture are stimulated [11,12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…e application of subthreshold electrical stimulation (ES) was reported to reduce postural sway in young healthy [11,17] and healthy elderly adults [15,18] and may consequently reduce the risk of falls in elderly persons. e reported studies differ in various features and protocols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation